2020
DOI: 10.3389/fphar.2020.00915
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia After Rituximab Administration in Steroid-Dependent Nephrotic Syndrome: A Case Report

Abstract: The monoclonal antibody rituximab is a commonly used steroid sparing agent for steroiddependent idiopathic nephrotic syndrome of childhood. With this brief report, we describe the first case of symptomatic hypokalemia after intravenous rituximab administration in a young woman. The sudden onset of dizziness and palpitation prompted acute lifethreatening hypokalemia recognition by blood gas analysis and electrocardiography. Her symptoms were rapidly controlled by intravenous potassium administration. Such adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hypokalemia is a significant adverse event in hospitalized patients that may trigger cardiac arrhythmias and/or respiratory arrest. Only one case of hypokalemia caused by rituximab administration has been reported in the literature as yet [ 15 ]. To reduce prednisone dependence, a young woman diagnosed with idiopathic NS was started on rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia is a significant adverse event in hospitalized patients that may trigger cardiac arrhythmias and/or respiratory arrest. Only one case of hypokalemia caused by rituximab administration has been reported in the literature as yet [ 15 ]. To reduce prednisone dependence, a young woman diagnosed with idiopathic NS was started on rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogammaglobulinemia is mostly present in children with low IgG levels, and low IgG levels and a previous history of SRNS are high risk factors for hypogammaglobulinemia after RTX treatment [31] , and most patients with hypogammaglobulinemia are complicated by infections [32] ; therefore, regular testing of immunoglobulins before and after RTX requires replacing immunoglobulins with individualized regimens [33] . Previous studies [34][35][36][37][38] have reported more specific adverse effects, including serum sickness, hypokalemia, hypersensitivity reactions, disseminated intravascular coagulation, and Crohn's disease.Kobayash et al [39] conducted a retrospective study to monitor the safety of RTX for RNS, adverse drug reactions were observed in 53.7% of patients, infections in 24% of patients, infusion reactions in 31.9% of patients, and no RTX-specific adverse reactions were observed, consistent with the known safety profile of RTX, which can be safely used in patients with RNS.…”
Section: Rituximab For Rnsmentioning
confidence: 99%